2013
DOI: 10.1186/1476-0711-12-39
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination, bacterial profile and antimicrobial susceptibility pattern of isolates from stethoscopes at Jimma University Specialized Hospital

Abstract: IntroductionHospital acquired infections are recognized as critical public health problems. Infections are frequently caused by organisms residing in healthcare environment, including contaminated medical equipment like Stethoscopes.ObjectiveTo determine bacterial contamination, bacterial profile and anti-microbial susceptibility pattern of the isolates from stethoscopes at Jimma University Specialized Hospital.MethodologyCross-sectional study conducted from May to September 2011 at Jimma University Specialize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
76
8
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(105 citation statements)
references
References 21 publications
17
76
8
4
Order By: Relevance
“…The percentage of contaminated stethoscopes (in Belgrade 98.4%, in Barcelona 100%) is similar to the information found in other studies of similar design (79%-100%) [10,11,12,13]. The data from Benha (46.67%) show that their stethoscopes are less drastically contami-…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The percentage of contaminated stethoscopes (in Belgrade 98.4%, in Barcelona 100%) is similar to the information found in other studies of similar design (79%-100%) [10,11,12,13]. The data from Benha (46.67%) show that their stethoscopes are less drastically contami-…”
Section: Discussionsupporting
confidence: 84%
“…The research showed that great majority (91.8%) physicians who took part don't disinfect their stethoscope frequently enough. The data don't differ from the information found in previous researches which show that 97%-100% physicians don't disinfect their stethoscopes regularly [10,11].…”
Section: Discussioncontrasting
confidence: 79%
“…Resultados semelhantes foram encontrados em hospitais da América do Norte, África, Oriente Médio, Índia e Reino Unido. 1,2,[5][6][7][8]15,16 Estudo realizado no Rio Grande do Sul demonstrou que a contaminação dos (50%), sendo a outra metade distribuída entre médicos preceptores, técnicos em enfermagem, médicos residentes, enfermeiros e fisioterapeutas (Tabela 1). Após a desinfecção dos estetoscópios com álcool gel, foi constatada uma redução de 71,44% da contaminação geral por microrganismos.…”
Section: Discussionunclassified
“…[5][6][7] Apesar de simples, a frequente deficiência na limpeza dos estetoscópios pode comprometera segurança dos pacientes e do próprio profissional de saúde. 1,2,8 A contaminação bacteriana de estetoscópios utilizados por profissionais de saúde pode ser superior a 80% e, o uso de álcool gel, iodopovidona (PVPI) 10%, álcool etílico hidratado 70% e clorexidina 4% mostraram-se efetivos na higienização e desinfecção.…”
Section: Background and Objectivesunclassified
“…The bacterial species isolated were gram positive bacteria (40%) like MRSA (14%), MSSA (12%), CNS (14%), whereas gram negative bacilli only one genus Klebsiella was isolated (20%) which is like the study conducted by Shiferaw T et al, where the gram positive cocci was isolated in more number of stethoscopes. 16 This might be because of the direct contact of stethoscopes to human skin flora, which contains mostly gram positive cocci. Also the life span of gram negative bacteria is not more than six hours invitro; the half life span is less than an hour.…”
Section: Discussionmentioning
confidence: 99%